VD_FINDINFO Pron / 2013 / 77 vom 27. März 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, RADIATION DU RÔLE, ASSISTANCE JUDICIAIRE, PROTECTION DE L'UNION CONJUGALE | 109 al. 1 CPC (CH), 122 CPC (CH), 123 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 241 CPC (CH)